Implementing Evidence‐Based Parenting Programmes in a Small Sample of English Urban Local Authorities: Eligibility, Fidelity and Intensity. (14th March 2012) - West, Anne; Mitchell, Louisa; Murphy, Tony
Abstract : This article focuses on the implementation of evidence‐based parenting programmes (EBPPs) in a small sample of urban local authorities in England. The first part discusses the development of government policy, guidance and implementation issues. The second part presents findings from an exploratory study, which focused on the implementation of EBPPs in terms of programme eligibility, fidelity and intensity in six urban local authorities. Implementation was not necessarily in line with policy or guidance. Issues associated with programme fidelity along with concerns about sustainability as a result of cuts in funding are discussed and implications for policy and future research considered.